2011
DOI: 10.1159/000332205
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and Stroke: Biomarker, Harbinger of Damage, and Therapeutic Target

Abstract: Inflammation is established as a contributor to cerebrovascular disease. Risk factors for stroke include many conditions associated with chronic or acute inflammation, and inflammatory changes in the brain after cerebrovascular events contribute to outcome in experimental studies, with growing evidence from clinical research. The brain is extremely susceptible to inflammatory challenge, but resident glia, endothelial cells and neurones can all mount a pronounced inflammatory response to infection or injury. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 195 publications
2
72
0
1
Order By: Relevance
“…23 IL-1β produced during cerebral injury may also contribute to immune depression by its effects on the hypothalamic-pituitary-adrenal axis, as corticotropin-releasing factor producing neurons were activated by IL-1, 108 and IL-1-mediated effects on the immune system in rodents were shown to depend on both activation of the sympathetic nervous system and release of corticotrophin-releasing hormone. 109 Moreover, IL-1 receptor antagonist reverses stroke-induced peripheral immunosuppression in patients, demonstrating that IL-1 activity is-at least partially-responsible for stroke-induced immunosuppression. 109,110 As Youm et al (2012) demonstrated, 111 agerelated increase in 'lipotoxic danger signals' such as free cholesterol and ceramides, leads to thymic caspase-1 activation via the Nlrp3 inflammasome.…”
Section: Different Organs Modulate Autoimmune Mechanisms In the Centrmentioning
confidence: 99%
See 1 more Smart Citation
“…23 IL-1β produced during cerebral injury may also contribute to immune depression by its effects on the hypothalamic-pituitary-adrenal axis, as corticotropin-releasing factor producing neurons were activated by IL-1, 108 and IL-1-mediated effects on the immune system in rodents were shown to depend on both activation of the sympathetic nervous system and release of corticotrophin-releasing hormone. 109 Moreover, IL-1 receptor antagonist reverses stroke-induced peripheral immunosuppression in patients, demonstrating that IL-1 activity is-at least partially-responsible for stroke-induced immunosuppression. 109,110 As Youm et al (2012) demonstrated, 111 agerelated increase in 'lipotoxic danger signals' such as free cholesterol and ceramides, leads to thymic caspase-1 activation via the Nlrp3 inflammasome.…”
Section: Different Organs Modulate Autoimmune Mechanisms In the Centrmentioning
confidence: 99%
“…109 Moreover, IL-1 receptor antagonist reverses stroke-induced peripheral immunosuppression in patients, demonstrating that IL-1 activity is-at least partially-responsible for stroke-induced immunosuppression. 109,110 As Youm et al (2012) demonstrated, 111 agerelated increase in 'lipotoxic danger signals' such as free cholesterol and ceramides, leads to thymic caspase-1 activation via the Nlrp3 inflammasome. Elimination of Nlrp3 and Asc, a critical adaptor required for inflammasome assembly, reduces age-related thymic atrophy.…”
Section: Different Organs Modulate Autoimmune Mechanisms In the Centrmentioning
confidence: 99%
“…The best-understood example of this is IL-1β, a proinflammatory cytokine associated with tissue damage via both inflammatory and noninflammatory genomic responses in neurons, glia, and the vasculature. 35 Antagonism of IL-1 with neutralizing antibodies (IL-1ra, anakinra) or by targeting the signaling pathway downstream of the receptor has shown considerable promise in rodent models. 35 A phase II trial has also suggested that the compound is safe and that clinical outcome may be improved by use of IL-1ra.…”
Section: Il-1mentioning
confidence: 99%
“…35 Antagonism of IL-1 with neutralizing antibodies (IL-1ra, anakinra) or by targeting the signaling pathway downstream of the receptor has shown considerable promise in rodent models. 35 A phase II trial has also suggested that the compound is safe and that clinical outcome may be improved by use of IL-1ra. 36 Like PSD-95, the case for IL-1Ra is strengthened by the multifaceted approach and adherence to STAIR criteria during its development, but phase III trials have not yet been conducted.…”
Section: Il-1mentioning
confidence: 99%
“…Human neuropathological studies and experimental animal models of perinatal brain injury revealed that pro-inflammatory cytokines, especially those from the IL-1 system, are implicated in the cascade leading to brain damage occurring at different developmental stages (Allan et al, 2005;Cai et al, 2004;Denes et al, 2011;Girard et al, 2008Girard et al, , 2010aHagberg et al, 1996;Kadhim et al, 2006Kadhim et al, , 2003Martin et al, 1994). In addition to their direct neurotoxic effects, cytokine imbalances are also suspected to affect brain development since cytokines play an active role in neurogenesis and synaptogenesis (Deverman and Patterson, 2009;Dziegielewska et al, 2000).…”
Section: Introductionmentioning
confidence: 99%